Evaluation of systemic inflammatory response syndrome-negative sepsis from a Chinese regional pediatric network - Yuanyuan Wang; Xiaofei Lin; Hongni Yue; Niranjan Kissoon; Bo Sun; Collaborative Study Group for Pediatric Sepsis in Huai'an (BMC, 2019)
Abstract Background The identification of sepsis in children varies depending on the definition used. Our purpose was to compare clinical data and outcome of atypical sepsis, manifested as having sepsis but not fulfilling the criteria of systemic inflammatory response syndrome (SIRS-negative sepsis, SNS), in children based on the modified Angus criteria with those of sepsis (S) and severe sepsis (SS) based on the international consensus criteria. Methods Pediatric departments in 11 regional city and county referral hospitals with emergency and intensive care settings in Huai'an serving for 843,000 children participated in a parallel multicenter prospective survey. Clinical data registry was used to recruit those who fulfilled the diagnostic criteria for pediatric sepsis from all admissions (n = 27,836) from 28 days to 15 years old, from September 1, 2010 to August 31, 2011. Results A total of 1606 children met the criteria for pediatric sepsis and were divided into three groups: S, (n = 1377), SS (n = 153, including 32 septic shock), based on the consensus definition criteria, and SNS (n = 76) based on the modified Angus criteria. Most deaths (38/54, 70.3%) occurred within three days of admission. The SNS mainly occurred in infants and was associated with cardiopulmonary and neurologic dysfunction without satisfying the SIRS criteria. Conclusions SNS differed from SS in that it predominantly affected infants and manifested with cardiopulmonary and neurologic dysfunction. There were no laboratory variables which were useful in identification of SNS, or predicting response to therapy or outcome.